Implikasi Kebijakan Pembatasan Pembiayaan dan Pengaruhnya terhadap Rasio Pembiayaan Bermasalah pada Bank Muamalat Indonesia Regional Sulawesi, Maluku, Papua - Sofhian Sofhian; Muh. Gifari Bachmid (Universitas Muhammadiyah Surabaya, 2023)
Abstract The purpose of this study is to find out what factors cause restrictions on the financing of funds, what are the implications of the Financing Restriction Policy at PT. Bank Muamalat Indonesia, Tbk Regional Sulawesi, Maluku, Papua The research method used is a qualitative method obtained from 10 branch offices in the SULAMPUA area, by conducting in-depth interviews with competent informants who provide accurate information through telephone interviews and other online media. The results of this study indicate that the financing restriction policy implemented by Bank Muamalat Indonesia Regional Sulampua, among others, is to improve the flow of the financing process by changing the limit of the financing breaker authority which was taken over by the head office financing division and revoking the branch office authority limit as a financing breaker, and removing all financing administration processes at branch offices because all financing processes must go through a centralized financing process that is centered on the Regional through Retail Financing Centers or Financing Operations, and most branch offices in the Sulampua Region are only allowed to carry out financing processes with low risk segments. The implication of this financing process is that it takes a long time, resulting in existing or new financing customers choosing to take over or move to another bank, the outstanding financing of BMI continues to decline. The centralization of the financing process resulted in the elimination of the existing financing administration functions at the branch offices and resulted in the transfer of employees who were previously in that position to the Regional Office in Makassar. Keywords; Implications, Financing Restrictions, Non-performing Financing Ratio